Reduced-tillage and Crop Productivity in Indian Arid Zone - Mohanram, Saritha; Kumar, Praveen; Panwar, Nav Raten; Burman, Uday (Annals of Arid Zone, 2022)
The increasing costs of energy, equipment, labor and the growing concernover soil loss have paved the way to development of reduced-tillage systems in placeof conventional tillage. These residue-retaining reduced-tillage systems are especiallyeffective in controlling soil erosion and substantially enhancing soil water storage. Thismodification of the soil microclimate by reduced-tillage exerts beneficial effects on thesoil microbial communities which plays a great role in nutrient transformations. Whileminimum tillage allows for minimal soil disturbance during field operations, no-tillagerefers to the complete absence of tillage. In practice, if one desires to reap equal orhigher yields and better environmental performance with minimum tillage than withconventional tillage systems, several components need to be applied to a conservationagriculture system. This can lead to variable yield responses with the minimum-/no-till management system, especially in a rainfed agro-ecology. Here we review thesuitability of reduced-tillage in arid regions, especially with reference to India whereexperiments on minimum tillage started in the early eighties. The results show limitedsuccess with this concept in Indian arid region, where climate and residue availabilityare a matter of concern. So, successful implementation of reduced-tillage systems as apotential solution to sustainable agricultural intensification needs 1) better understandingof crop and environmental variables and 2) appropriate adoption measures with ampleinstitutional and technology support, over a long term.